Parasitic Oscillations in Coaxial Gyrotron Beam Tunnels - Moraitou, M. D.; Latsas, G. P.; Ioannidis, Z. C.; Tigelis, I. G. (Electron Devices, IEEE Transactions on, 2013)
High-power high-frequency gyrotrons are required for several applications, including plasma heating, current drive, and plasmas stabilization for controlled thermonuclear fusion. Despite the use of dumping dielectric material in these gyrotrons, parasitic oscillations often appear, which significantly affect their operation and efficiency. In this paper, we perform an extended parametric study on the effect of the beam-tunnel characteristics, i.e., the outer radius of the inner waveguide and the width of the grooves, as well as the lossy material properties and the beam-radial position on the dumping of these oscillations.
Keywords: beam-radial position; beam-tunnel characteristics; Cavity resonators; Ceramics; Coaxial gyrotron beam tunnel; coaxial gyrotron beam tunnels; controlled thermonuclear fusion; current drive; Dielectrics; dumping dielectric material; dumping material losses; extended parametric study; Geometry; gyrotrons; high-power high-frequency gyrotrons; inner waveguide; lossy material properties; oscillations; Oscillators; parasitic oscillations; plasma heating; plasma instability; plasmas stabilization